A low-energy consumption activated carbon physical and chemical activation method based on homogeneous liquid phase impregnation
Patent Information
- Application Number
- CN202611333234.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]本发明的目的在于提供一种基于均匀液相浸渍的低能耗活性炭物理化学活化方法,旨在改善现有常规液相浸渍工艺中活化剂析出不均、碳源与低掺量活化剂混合均匀度差的问题
[0024]1、本发明通过固定水溶液混合与均匀加热,解决了样品干燥过程中水溶液非均匀蒸发导致的活化剂浸渍浓度不均匀、浸渍效果差的问题,在使用少量活化剂的条件下保障了活性炭发达孔隙结构的有效构筑。
Smart Images

Figure CN123002843A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of activated carbon preparation technology, specifically to a low-energy-consumption physicochemical activation method for activated carbon based on uniform liquid phase impregnation. Background Technology
[0002] Activated carbon, with its well-developed pore structure, high specific surface area, good mechanical strength, and chemical stability, is an important industrial material widely used in energy, environmental protection, and chemical industries. Currently, commercially available activated carbon with a well-developed pore structure and a specific surface area > 600 m²·g⁻¹ can be obtained using mature heat treatment methods.
[0003] Among various activated carbon preparation methods, physicochemical activation has attracted much attention due to its low dosage and well-developed pores of activating agents such as KOH, K2CO3, NaOH, and Na2CO3. However, the non-uniform mixing of carbon sources (mainly coal and biomass) and a small amount of activating agent in industrial processes makes it difficult to effectively utilize the pore-forming advantages of the activating agent, which is a significant technical bottleneck for the large-scale production of activated carbon.
[0004] Currently, the main methods for mixing activators and carbon sources include conventional physical mixing (powder mixing), ball milling physical mixing, liquid phase impregnation, and high-temperature melt impregnation. Among these, conventional physical mixing is difficult to achieve uniform mixing of a large amount of carbon source with a small amount of activator. Ball milling physical mixing is limited by long mixing time and small mixing volume. High-temperature melt impregnation is suitable for scenarios where a large amount of activator (≥ 10 wt.%) is mixed with a carbon source, but it has the problems of high heating energy consumption and high power consumption to maintain a vacuum environment.
[0005] Compared to the mixing methods mentioned above, liquid-phase impregnation has the advantages of simple operation and low operating cost. However, for liquid-phase impregnation methods involving small amounts of activator, problems such as uneven heating, high liquid evaporation, and slow carbon source drying can easily lead to uneven precipitation and mixing of the activator.
[0006] Therefore, developing a liquid-phase impregnation method that can stably achieve uniform mixing of a small amount of activator and carbon source, based on conventional liquid-phase impregnation, is key to promoting the industrial application of physicochemical activation methods in the field of activated carbon preparation. Summary of the Invention
[0007] The purpose of this invention is to provide a low-energy-consumption physicochemical activation method for activated carbon based on uniform liquid phase impregnation, aiming to improve the problems of uneven activator precipitation and poor uniformity of mixing between carbon source and low-dosage activator in existing conventional liquid phase impregnation processes.
[0008] This invention is implemented as follows:
[0009] A low-energy-consumption physicochemical activation method for activated carbon based on homogeneous liquid phase impregnation, such asFigure 1 As shown, it includes the following steps:
[0010] S100: Crushing and screening the carbon raw material to obtain particles of a specific size;
[0011] S200: A certain mass of granules is added to a certain amount of aqueous solution with a fixed activator concentration and placed in a drying device;
[0012] S300. After drying, transfer the solid particles to the reactor.
[0013] S400: The target activated carbon is obtained by heating solid particles under a nitrogen atmosphere or an activating atmosphere.
[0014] Furthermore, in step S100, the charcoal raw material is coal and biomass, including one or a mixture of several of lignite, bituminous coal, weakly caking or non-caking coal, corn stalks, and walnut shells.
[0015] Furthermore, in step S100, the particle size of the crushed and screened particles is 0.03 mm to 2 mm.
[0016] Furthermore, in step S100, the activator is an alkaline activator or a metal salt. The alkaline is one or a mixture of sodium hydroxide and potassium hydroxide, and the metal salt activator is one or a mixture of sodium carbonate, potassium carbonate, and calcium chloride. The mass of the activator is 0.1 to 3.0 wt. of the carbon source mass.
[0017] Furthermore, in step S200, the mass ratio of the aqueous solution to the carbon source is 0.2:1 to 2:1.
[0018] Furthermore, in step S200, the concentration of the activator in the aqueous solution is 1 g / L to 30 g / L.
[0019] Furthermore, in step S200, the aqueous solution is added by a fixed mass or by a flow-through method to ensure that the concentration of the aqueous solution is consistent and stable in all regions within the carbon raw material particle area.
[0020] Furthermore, in step S300, the thickness of the dried carbon source particles is 1 mm to 30 mm, the drying temperature is 80 to 150°C, and the drying time is 10 to 24 h.
[0021] Furthermore, in step S400, the temperature in the reactor is raised to 700-900°C at a heating rate of 2-10°C·min⁻¹ and stabilized for 5-360 min; nitrogen gas is introduced to maintain an inert atmosphere, with a nitrogen flow rate of 0.1-10 L·min⁻¹; the activation atmosphere is one or more of CO₂, H₂O, and O₂ introduced on the basis of nitrogen gas, and the concentration of the activation component in the activation atmosphere is 10-80 vol.%.
[0022] Furthermore, the reactor is a tubular furnace, a pusher furnace, or a rotary kiln.
[0023] Compared with the prior art, the beneficial effects of the present invention are:
[0024] 1. This invention solves the problem of uneven concentration and poor impregnation effect of activator caused by non-uniform evaporation of aqueous solution during sample drying by fixing the mixing of aqueous solution and uniform heating. It ensures the effective construction of the well-developed pore structure of activated carbon under the condition of using a small amount of activator.
[0025] 2. By adding a quantitative aqueous solution, this invention can effectively control the energy consumption of the sample drying process and reduce the energy cost in the activated carbon production process.
[0026] 3. The activated carbon preparation method proposed in this invention is based on the industrially mature carbonization-activation process. This technical route for activated carbon preparation has good application prospects and industrialization potential. Attached Figure Description
[0027] Figure 1 This is a flowchart of the method of the present invention;
[0028] Figure 2 This is a schematic diagram of a conventional liquid-phase impregnation activator-carbon source mixing method;
[0029] Figure 3 This is a schematic diagram of the fixed mass ratio addition method in the uniform liquid phase impregnation method of the present invention;
[0030] Figure 4 This is a schematic diagram of the aqueous solution flow and addition method in the uniform liquid phase impregnation method of the present invention;
[0031] Figure 5 This is a nitrogen adsorption isotherm diagram of the activated carbon obtained in the embodiments and comparative examples of the present invention. Detailed Implementation
[0032] The following description, in conjunction with the accompanying drawings, specific embodiments, and comparative examples, provides further details:
[0033] Raw materials and equipment used in the examples and comparative examples:
[0034] Charcoal raw materials: Zhundong bituminous coal (Zhundong region of Xinjiang Uygur Autonomous Region), walnut shells, and corn stalks, all of which are industrial grade.
[0035] Activators: Sodium carbonate, potassium hydroxide, potassium carbonate.
[0036] Drying equipment: Electric heating forced-air drying oven (temperature range: room temperature ~ 250°C).
[0037] Activation reactor: Laboratory horizontal tube furnace or rotary kiln (as described in the examples).
[0038] Gases: Nitrogen, 99.99% purity; carbon dioxide, 99.9% purity; water vapor, generated from deionized water.
[0039] Analysis and testing methods:
[0040] The specific surface area and total pore volume of activated carbon were determined using a nitrogen adsorption-desorption apparatus.
[0041] Comparative Example 1
[0042] This comparative example uses a conventional liquid phase impregnation method, such as Figure 2 As shown, the total amount of aqueous solution and the thickness of the dry stack are not controlled.
[0043] Step 1: Crush and screen the Zhundong sub-bituminous coal, and take coal particles of 20-40 mesh for later use.
[0044] Step 2: Weigh 100g of coal particles into a 1L beaker, add 500mL of sodium carbonate aqueous solution with a concentration of 2g / L (the activator mass is 1.0% of the coal particle mass), and stir well.
[0045] Step 3: Place the beaker in a drying oven and dry at 90°C for 24 hours. During the drying process, the particles will naturally accumulate to a thickness of 20 mm without any thinning treatment.
[0046] Step 4: Place the dried sample in a rotary kiln, using a nitrogen flow of 150 mL·min⁻¹ as the carrier gas, and raise the temperature from room temperature to 900°C at a rate of 10°C·min⁻¹. Then, turn on the steam generator and introduce steam (activation atmosphere) into the rotary kiln at a rate of 1 g·min⁻¹, and activate at 900°C for 60 min. After activation, allow it to cool naturally to room temperature under a nitrogen atmosphere to obtain activated carbon, denoted as AC-1.
[0047] AC-1's performance: specific surface area 528 m²·g⁻¹, total pore volume 0.25 cm³·g⁻¹.
[0048] Comparative Example 2
[0049] This comparative example is used to compare the effect of conventional liquid phase impregnation under high activator dosage, in order to verify the superiority of the present invention under low dosage.
[0050] Step 1: Crush and screen the Zhundong sub-bituminous coal, and take coal particles of 20-40 mesh for later use.
[0051] Step 2: Weigh 100g of coal particles into a 1L beaker, add 500mL of sodium carbonate aqueous solution with a concentration of 20g / L (the activator mass is 10.0% of the coal particle mass), and stir well.
[0052] Step 3: Place the beaker in a drying oven and dry at 90°C for 24 hours. During the drying process, the particles will naturally accumulate to a thickness of 20 mm without any thinning treatment.
[0053] Step 4: Place the dried sample in a rotary kiln, using a nitrogen flow of 150 mL·min⁻¹ as the carrier gas, and raise the temperature from room temperature to 900°C at a rate of 10°C·min⁻¹. Then, turn on the steam generator and introduce steam (activation atmosphere) into the rotary kiln at a rate of 1 g·min⁻¹, and activate at 900°C for 60 min. After activation, allow it to cool naturally to room temperature under a nitrogen atmosphere to obtain activated carbon, denoted as AC-5.
[0054] AC-5 performance: specific surface area 858 m²·g⁻¹, total pore volume 0.48 cm³·g⁻¹.
[0055] Example 1
[0056] This embodiment employs the fixed mass ratio addition method in the uniform liquid phase impregnation method provided by the present invention: a fixed ratio of aqueous solution mass to carbon raw material mass, and thin-layer stacking drying, such as... Figure 3 As shown.
[0057] Step 1: Crush and screen the Zhundong sub-bituminous coal, and collect coal particles of 20-40 mesh for later use. Same as Comparative Example 1 and Comparative Example 2.
[0058] Step 2: Weigh 100g of coal particles and place them in an evaporating dish. Prepare 200mL of a 5g / L sodium carbonate aqueous solution (the activator mass is 1.0% of the coal particle mass), with the aqueous solution mass to carbon raw material mass ratio of 2:1. After mixing the coal particles and aqueous solution evenly, divide the mixture into 10 evaporating dishes, with the particle thickness in each dish being 2mm.
[0059] Step 3: Place all evaporating dishes in a drying oven and dry at 90°C for 24 hours to obtain dried samples.
[0060] Step 4: Place the dried sample in a rotary kiln and activate it under the same conditions as Comparative Example 1 (150 mL·min⁻¹ nitrogen, 10°C·min⁻¹ heating to 900°C, 1 g·min⁻¹ water vapor, 60 min activation, and natural cooling) to obtain activated carbon, denoted as AC-2.
[0061] AC-2 performance: specific surface area 962 m²·g⁻¹, total pore volume 0.48 cm³·g⁻¹.
[0062] Compared with Comparative Example 1: Under the same activation conditions, only the impregnation and drying method was changed, the specific surface area and pore volume of AC-2 increased by 82.2% and 92.0% respectively compared with Comparative Example 1 (AC-1), indicating that the method of the present invention significantly improves the pore-forming efficiency of the activator.
[0063] Compared with Comparative Example 2: Comparative Example 2 used 10 times the amount of activator of the present invention (10 wt.% vs. 1 wt.%), but the specific surface area (858 m²·g⁻¹) and pore volume (0.48 cm³·g⁻¹) of the resulting activated carbon AC-5 were still lower than those of AC-2 in Example 1 (962 m²·g⁻¹, 0.48 cm³·g⁻¹). This shows that the method of the present invention achieves a pore structure (especially a high proportion of micropores) that surpasses conventional methods with high amounts of activator with extremely low amounts of activator.
[0064] Example 2
[0065] This embodiment verifies the universality of the method of the present invention for different carbon sources and different activators.
[0066] Step 1: Crush and sieve the walnut shells to obtain 30-60 mesh particles for later use.
[0067] Step 2: Place the walnut shells in a box furnace and heat them from room temperature to 350°C at a nitrogen flow rate of 0.5 L·min⁻¹ and a heating rate of 5°C·min⁻¹. Hold the temperature for 60 minutes and then allow them to cool naturally under a nitrogen atmosphere to obtain pre-carbonized material.
[0068] Step 3: Weigh 100g of pre-carbonized material and prepare 150mL of a 6.7g / L potassium hydroxide aqueous solution (the mass of the activator is 1.0% of the mass of the carbon raw material), with the mass ratio of the aqueous solution to the carbon raw material being 1.5:1. After mixing the walnut shell particles with the aqueous solution evenly, divide the mixture into 5 evaporating dishes, with a thickness of 3mm in each dish.
[0069] Step 4: Place the evaporating dish in a drying oven and dry at 105°C for 12 hours to obtain a dried sample.
[0070] Step 5: Place the dried sample in a rotary kiln and heat it from room temperature to 900°C at a nitrogen flow rate of 0.5 L·min⁻¹ and a heating rate of 10°C·min⁻¹, holding it at that temperature for 60 min in a mixed atmosphere (20 vol.% CO₂ + 80 vol.% N₂). After activation, allow it to cool naturally under a nitrogen atmosphere to obtain activated carbon, denoted as AC-3.
[0071] AC-3 performance: specific surface area 940 m²·g⁻¹, total pore volume 0.44 cm³·g⁻¹.
[0072] The results show that the method of the present invention is also applicable to biomass carbon sources (walnut shells) and alkali activators (KOH), and can obtain activated carbon with high specific surface area.
[0073] Example 3
[0074] This embodiment verifies another uniform impregnation method in the present invention: the aqueous solution is added in a flowing manner, such as... Figure 4 As shown. This method is suitable for continuous production. It involves slowly flowing an aqueous solution with a fixed activator concentration through a layer of carbon raw material particles to maintain a consistent solution concentration in each area, followed by thin-layer drying.
[0075] Step 1: Crush and screen the Zhundong coal to obtain particles of 20-60 mesh for later use.
[0076] Step 2: Weigh 100g of Zhundong coal particles and place them in a cylindrical container equipped with a sieve plate or filter paper. Prepare 100mL of a 20g / L sodium carbonate aqueous solution (the activator mass is 1.0% of the carbon raw material mass). Flow the aqueous solution from top to bottom through the particle layer at a flow rate of approximately 5mL / min, ensuring that all particles are in full contact with the solution and that the solution concentration remains uniform throughout. After all the solution has flowed out, remove the particles and distribute them into 8 evaporating dishes, with a stack thickness of 2.5mm.
[0077] Step 3: Place the evaporating dish in a drying oven and dry at 90°C for 15 hours.
[0078] Step 4: Place the dried sample in a rotary kiln and activate it under the same conditions as Comparative Example 1 (150 mL·min⁻¹ nitrogen, 10°C·min⁻¹ heating to 900°C, 1 g·min⁻¹ steam, 60 min activation, and natural cooling) to obtain activated carbon, denoted as AC-4.
[0079] AC-4 performance: specific surface area 898 m²·g⁻¹, total pore volume 0.48 cm³·g⁻¹.
[0080] The results show that the uniform impregnation of the activator can also be achieved by adding the activator in an aqueous solution, and the resulting activated carbon has a high specific surface area and a well-developed pore structure, with performance comparable to that of the fixed mass ratio addition method.
[0081] The following is a summary table comparing the various comparative examples and embodiments:
[0082] AC-1 (Comparative Example 1) Zhundong sub-bituminous coal Sodium carbonate, accounting for 1.0 wt.% of the raw material. Conventional liquid phase impregnation without controlling the total solution volume 20mm 528 0.25 AC-5 (Comparative Example 2) Zhundong sub-bituminous coal Sodium carbonate, accounting for 10.0 wt.% of the raw material. Conventional liquid phase impregnation without controlling the total solution volume 20mm 858 0.48 AC-2 (Example 1) Zhundong sub-bituminous coal Sodium carbonate, accounting for 1.0 wt.% of the raw material. Fixed liquid mass ratio immersion 2mm 962 0.48 AC-3 (Example 2) walnut shell Potassium hydroxide, accounting for 1.0 wt.% of the raw material. Fixed liquid mass ratio immersion 3mm 940 0.44 AC-4 (Example 3) Zhundong sub-bituminous coal Sodium carbonate, accounting for 1.0 wt.% of the raw material. Aqueous solution flow and impregnation 2.5mm 898 0.48
[0083] The comparison of the above comparative examples and embodiments shows that:
[0084] 1) Shortcomings of conventional liquid phase impregnation: Even when using the same low amount of activator, Comparative Example 1 showed low activator utilization and underdeveloped pore structure of the obtained activated carbon due to uneven evaporation of the aqueous solution and non-uniform precipitation of the activator on the particle surface during the drying process.
[0085] 2) Limitations of high activator dosage: Comparative Example 2 increased the activator dosage to 10%, which could partially improve the pore structure, but it was far from reaching the level of the low dosage of this invention, and it significantly increased the raw material cost and subsequent processing burden.
[0086] 3) Significant effects of the method of the present invention: In Examples 1 to 3, the method of the present invention was used. By controlling the mass ratio of aqueous solution to carbon raw material and thin-layer stacking drying, low-concentration activator can be uniformly precipitated and penetrate into the interior of the particles, and finally activated carbon products with well-developed pore structure are obtained.
[0087] 4) Comparison of nitrogen adsorption isotherms: such as Figure 5 As shown, the nitrogen adsorption isotherms of activated carbon AC-2 obtained in Example 1 showed significantly higher adsorption capacities at all relative pressures (P / P0) than those of AC-1 in Comparative Example 1. In the low-pressure region (P / P0 < 0.1), the adsorption capacity of AC-2 increased sharply, indicating its rich microporous structure. In the medium-high pressure region (P / P0 > 0.4), the adsorption capacity of AC-2 continued to increase and a significant hysteresis loop appeared, indicating that it also contains a mesoporous structure. In contrast, the adsorption capacity of AC-1 was low across the entire pressure range, indicating an underdeveloped pore structure. This comparison clearly demonstrates the significant improvement in the pore structure of activated carbon achieved by the method of this invention.
[0088] The above are merely preferred embodiments of the present invention and are not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A low-energy-consumption physicochemical activation method for activated carbon based on homogeneous liquid phase impregnation, characterized in that, Includes the following steps: S100: Crushing and screening the carbon raw material to obtain particles of a specific size; S200: A certain mass of granules is added to a certain amount of aqueous solution with a fixed activator concentration and placed in a drying device; S300. After drying, transfer the solid particles to the reactor. S400: The target activated carbon is obtained by heating solid particles under a nitrogen atmosphere or an activating atmosphere.
2. The low-energy-consumption physicochemical activation method for activated carbon based on uniform liquid phase impregnation according to claim 1, characterized in that, In step S100, the charcoal raw material is coal and biomass, including one or a mixture of several of lignite, bituminous coal, weakly caking or non-caking coal, corn stalks, and walnut shells.
3. The low-energy-consumption physicochemical activation method for activated carbon based on uniform liquid phase impregnation according to claim 1, characterized in that, In step S100, the particle size of the crushed and screened particles is 0.03 mm to 2 mm.
4. The low-energy-consumption physicochemical activation method for activated carbon based on uniform liquid phase impregnation according to claim 1, characterized in that, In step S100, the activator is an alkaline activator or a metal salt. The alkali is one or a mixture of sodium hydroxide and potassium hydroxide, and the metal salt activator is one or a mixture of sodium carbonate, potassium carbonate, and calcium chloride. The mass of the activator is 0.1 to 3.0% of the mass of the carbon raw material.
5. The low-energy-consumption physicochemical activation method for activated carbon based on uniform liquid phase impregnation according to claim 1, characterized in that, In step S200, the mass ratio of the aqueous solution to the carbon raw material is 0.2:1 to 2:
1.
6. The low-energy-consumption physicochemical activation method for activated carbon based on uniform liquid phase impregnation according to claim 1, characterized in that, In step S200, the concentration of the activator in the aqueous solution is 1 g / L to 30 g / L.
7. The low-energy-consumption physicochemical activation method for activated carbon based on uniform liquid phase impregnation according to claim 1, characterized in that, In step S200, the aqueous solution is added by either fixed mass addition or flow addition, so that the concentration of the aqueous solution in each region within the carbon raw material particle range is consistent and remains stable.
8. The low-energy-consumption physicochemical activation method for activated carbon based on uniform liquid phase impregnation according to claim 1, characterized in that, In step S300, the thickness of the dried charcoal raw material particles is 1 mm to 30 mm, the drying temperature is 80 to 150°C, and the drying time is 10 to 24 h.
9. The low-energy-consumption physicochemical activation method for activated carbon based on uniform liquid phase impregnation according to claim 1, characterized in that, In step S400, the reactor is heated at 2~10°C / min. -1 The temperature was increased to 700–900°C and stabilized for 5–360 min; nitrogen gas was introduced to maintain an inert atmosphere at a flow rate of 0.1–10 L / min. -1 The activation atmosphere is one or more of CO2, H2O, and O2 introduced into the nitrogen atmosphere, and the concentration of the activation component in the activation atmosphere is 10-80 vol.%.
10. The low-energy-consumption physicochemical activation method for activated carbon based on uniform liquid phase impregnation according to claim 1, characterized in that, The reactor is a tubular furnace, a pusher furnace, or a rotary kiln.
